The Union of Utrecht: Its Genesis and Consequences - Вoogman J. C. (Czasopismo Prawno-Historyczne, 1980)
In the former chapter-hall of the cathedral serving now as auditorium for the University of Utrecht, the Union of Utrecht was founded on 23rd January 1579. Before discussing the functioning of the federal system of the Republic of the United Provinces, I shall devote some attention to the formation of the Union resulting in the federal incorporation of the seven provinces into the Republic of the United Netherlands. The young Pieter Paulus, who in the years 1775-1777 published a commentary on the Union which has since become famous, described it as the Bulwark of our Liberty, the joyous Mother of so many blessings, the Cultivator of the prestige of this Republic at. the principal courts of Europe, and as base of that Pyramid, to which eminent men have compared this State.